Growing Turfgrass in the Shade - Laurie E. Trenholm (EDIS)
Revised! ENH-151, a 2-page fact sheet by L.E. Trenholm, lists species of turfgrass suitable for use in the shade and management practices to minimize added stress. Published by the UF Department of Environmental Horticulture, April 2008.